In-Depth Review of PT. Penta Cosmopolitan CSR Program: TKIT Syeikh Abdurrauf Education Facility, Banda Aceh - Bijaksana, Rizky Pradana; Rudito, Bambang (Journal of Business and Management, 2014)
The tsunami that occurred in the year 2004 nearly leveled the city of Banda Aceh and surrounding areas . Of course, infrastructure and public facilities damaged thereby , including schools and other educational institutions in the form . Various aid comes from a variety of parties , including the private company . These companies make community development programs or in this case , the reconstruction , which is formed in the form of Corporate Social Responsibility . Assist and fund community to solve various problems and meet the needs of the population in the surrounding area concerned . This final project is written for review and in-depth understanding of the CSR programs conducted by PT . Penta Cosmopolitan . Is engaged in property and education , the private companies also helped in the development of post-tsunami Aceh region in the field of educational facilities . The author used direct and personal approach to the program established by PT . Penta Cosmopolitan . Among others the way proceeds go directly to the location of the program is TKIT / Taam Sheikh Abdurrauf . Located in the village of Blang Oi , Meuraxa district , this village is one of the villages worst affected by the tsunami . In this thesis , will be included history , process and details of the CSR program between PT . Penta Cosmopolitan and Abdurrauf Sheikh 's Foundation . All observations and interviews with relevant parties will also be included in this thesis . The ultimate purpose of this final project is to observe objectively from the program . Finally, the authors hope that the recommendations and suggestions of the writers will make this program become better in the futureÂ